Types of domestic violence in Pakistan: Elaborating on Johnson’s typology - Nawaz, Bela (Journal of family violence, 2024)
PurposeThe present study applies Johnson’s (2008) typology of intimate partner violence (IPV) to female survivors in Karachi, Pakistan.MethodFace-to-face structured interviews of a purposive sample of 80 ever-married survivors of IPV, followed by a cluster analysis of husbands’ controlling behaviors to identify types of IPV, followed by quantitative exploration of differences among the types.ResultsThe first type identified by a Ward’s method cluster analysis is situational couple violence (SCV), comprising 29 respondents whose husbands exhibited low levels of control for all items. The second type is intimate terrorism (IT), comprising 15 respondents experiencing high levels of control on most items. The third type, unique to this study, is labeled as familial intimate terrorism (FIT) and consists of 36 respondents whose husbands were not quite as controlling as IT, not particularly jealous or sexually cruel, but more likely than IT to use control tactics that were based in the joint family system.ConclusionsThe Johnson control typology does, indeed, apply to intimate partner violence in Pakistan, with the important addition of a third type of male violence, rooted in the joint family system that is prevalent in many countries around the world. In future research, it would be important to include a sample of non-violent couples for comparison, especially important in cultures in which the joint family system authorizes considerable “normal” control over women. Although we have assumed that the newly-identified type (familial intimate terrorism) involves men (and sometimes their families) abusing the norms of this system, further exploration of this issue is necessary.